Persepsi Layanan perbankan syariah menurut Kiai dan Asatidz (Studi Ponpes Syifaul Qulub Kecamatan Tebo) - Adi, Rachmadi Setiawan (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2022)
This study aims to determine the perceptions of Kiai and Asatidz at the Syifaul Qulub Islamic boarding school, Tebo district, toward Islamic banking service. This study used a qualitative approach with data collection methods through interviews, observation and documentation. The type of research used is primary and secondary by utilizing data obtained from the field and written data in the form of reports and documentation. This study uses indicators such as responses, opinions and assessments which are used as a reference for formulating problems related to the discussion of the perceptions of Kiai and Asatidz. Based on the research conducted, the results obtained were that there were various kinds of perceptions or views of Kiai and Asatidz regarding Islamic banking. Especially on the knowledge of Kiai and Asatidz who are still not good about islamic banks. So that among them there are still many who have not used Islamic bank. The author hopes that this research will be a positive update related to cases of problems that occur in the perceptions of kiai and Asatidz. So that in the future they can experience better progress toward knowledge of islamic bank and they are more aware of the existence of these Islamic banks. Keyword: Perception, Islamic Bank Service